IFDi won gold at IID Johor 2017 - Joseph, Corina (Universiti Teknologi MARA, Sarawak, 2017)
A group of Faculty of Accountancy, UiTM Sarawak lecturers won a gold award at the International Invention, Innovation and Design Competition (HD Johor) held at Amansari Residence Resort, Johor on 9 March 2017. The product exhibited was The Integrity Framework Disclosure Index (IFDi), a system consisting of 50 items developed from the circular issued by the Malaysian Secretary General of the Ministry of Housing and Local Government, western countries public sector integrity framework and observations of twenty Malaysian local authority websites. The system can be used to measure the level of commitment of public sector organizations towards minimizing the unethical conducts using the disclosure practice. This IFDi could be used to indicate the level of integrity in the local authorities, instill positive values among stakeholders and promote ethical conducts among the society members at large as a result of increased awareness benefitted from the disclosure. The project is led by Associate Professor Dr. Corina Joseph and the members are Mariam Rahmat, Tamoi Janggu, Nero Madi and Professor Dr. Nafsiah Mohamed. The project is sponsored by the Accounting Research Institute (ARI), a Higher Institution of Centre of Excellence (HiCoE) under the Ministry of Higher Education, Malaysia.